ALIRAN AIR SEBAGAI PEMBENTUK TOPONIMI KELURAHAN/DESA DI KOTA BANJARMASIN DAN KABUPATEN BANJAR: KAJIAN EKOLINGUISTIK - Yuliati Puspita Sari (Balai Bahasa Kalimatan Selatan, 2018)
This study discusses the influence of stream as the toponymy creator of village in Banjarmasin City and Banjar Regency. This study aims to (a) describe various forms of lexicons related stream and elements that can unite stream in forming village stream toponymy in Banjarmasin City and Banjar Regencies; (b) describe the interaction that occur between the natural environment and language in forming village toponymy in Banjarmasin City and Banjar Regency. This study uses qualitative methods and ecolinguistic approach. The results of the study show that there are various lexicons associated with stream that are used as forming toponymy, they are sungai, riam, antasan, handil, and tatah. Meanwhile, judging from the merging pattern, there are various elements that can unite the lexicon which is related to the stream, flow of water, including plants, animals, colors, professions / jobs, and so on. The interaction which is happened between nature and language has big influence toward toponymy of the village in both territory.